Uterine Fibroid Embolisation – Potential Impact on Fertility and Pregnancy Outcome - David, M.; Kröncke, T. (Geburtshilfe und Frauenheilkunde, 2013)
The current standard therapy to treat myomas in women wishing to have children consists of minimally invasive surgical myomectomy. Uterine artery embolisation (UAE) has also been discussed as another minimally invasive treatment option to treat myomas. This review evaluates the literature of the past 10 years on fibroid embolisation and its impact on fertility and pregnancy. Potential problems associated with UAE such as radiation exposure of the ovaries, impairment of ovarian function and the impact on pregnancy and child birth are discussed in detail. Previously published reports of at least 337 pregnancies after UAE were evaluated. The review concludes that UAE to treat myomas can only be recommended in women with fertility problems due to myomas who refuse surgery or women with an unacceptably high surgical risk, because the evaluated case reports and studies show that UAE significantly increases the risk of spontaneous abortion; there is also evidence of pathologically increased levels for other obstetric outcome parameters. There are still very few prospective studies which provide sufficient evidence for a definitive statement on the impact of UAE therapy on fertility rates and pregnancy outcomes.
Keywords: embolisation; myoma; fertility; pregnancy; birth